Full-scale insight into high-entropy ceramics from basic concepts, synthesis technologies, structural characteristics, and properties to application prospects - Yunlei Wang; Jie Zhang; Taibin Wu; Guangjie Huang (Journal of Materials Research and Technology)
High-entropy ceramics (HECs) are an emerging material system that has gained significant attention and become a focal point of research due to their unique structure and outstanding performance. This paper provides a comprehensive examination of the basic concepts, synthesis methods, structural characteristics, unique properties, and application prospects of HECs. It begins with an overview of the basic concepts and historical context, followed by a detailed comparison of synthesis techniques, including both traditional and innovative approaches. The paper then analyzes the structural characteristics and phase compositions of HECs, particularly focusing on oxide, carbide, boride, and other non-oxide ceramics. In addition, it delves into the mechanical, thermal, electrical, and magnetic properties of HECs. The article also reviews the applications of HECs in high-temperature structural materials, functional materials, high-performance coatings, and biomedical implants. Finally, it discusses the future challenges and development pathways for HECs. By highlighting new applications and transformative possibilities, this study not only sheds light on cutting-edge research but also emphasizes the significant impact of HECs on sustainable material development. The integration of machine learning and artificial intelligence can further unlock the unique structural capabilities of HECs, offering substantial potential for advancements in emerging fields like new energy and biomedicine.